2014
DOI: 10.1016/j.jadohealth.2013.12.023
|View full text |Cite
|
Sign up to set email alerts
|

A Peer Education Program: Delivering Highly Reliable Sexual Health Promotion Messages in Schools

Abstract: Teen PEP developers have been able to successfully adapt and replicate it in North Carolina, in settings that need sexual health education services for youth both because of the paucity of existing services in many areas and because of the evidence of risk in the form of high rates of pregnancy and sexually transmitted infections, including human immunodeficiency virus or AIDS in youth 15-19 years of age. Youth reported benefits across a range of social and sexual health-related areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 6 publications
1
46
0
8
Order By: Relevance
“…Moreover, adolescents in different societies face problems when attempting to acquire appropriate information about their age-related concerns (6). Therefore, there is a need for designation of appropriate educational programs to meet their needs (7).…”
Section: Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, adolescents in different societies face problems when attempting to acquire appropriate information about their age-related concerns (6). Therefore, there is a need for designation of appropriate educational programs to meet their needs (7).…”
Section: Contextmentioning
confidence: 99%
“…Peer education can be implemented for different age groups (16) with the aim of improving knowledge, changing attitudes and beliefs (17), and supporting and empowering participants to make informed decisions (7). Many studies have shown that peer education was an acceptable approach of education of adolescents, and could improve their knowledge and attitudes (17).…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…(Demissie Z, 2013;Layzer, Rosapep, & Barr, 2014). One of the teen health programs conducted at the school is the Centre for Information and Counseling (PIK-in Bahasa) for teenagers/students or school-based peer education (BKKBN, 2012;Jones, 2012;Story & Gorski, 2013).…”
Section: Introductionmentioning
confidence: 99%